Does the Pan‑European Personal Pension Product Suit All? Its Perspectives in the EU Member and Candidate Countries - Kochaniak, Katarzyna; Korzeniowska, Anna Magdalena; Huterska, Agnieszka Anna; Demirhan, Dilek; Susmuş, Türker (Comparative Economic Research. Central and Eastern Europe, 2023)
This article aims to verify the development prospects of the Pan‑European Personal Pension Product (PEPP) in the European Union (EU). It focuses on the relationship between the quality of domestic public pension schemes and household savings for old age in the EU member and candidate countries. The study was conducted in two stages. The first stage examined the interrelationship between public pension schemes and household savings based on Pearson’s correlation coefficients. In the second stage, sub‑samples of countries with high and low‑quality public pension schemes were identified using hierarchical cluster analysis. The results showed significant links between households’ obligatory and voluntary saving for retirement in both samples. However, the study recognised the internal diversity of countries in terms of households’ preferences for the types of financial assets. Based on these findings, conclusions about the development potential of PEPP are drawn. The best prospects are identified for Croatia, Cyprus, France, Greece, Hungary, Poland, Portugal, Romania, Slovenia, Spain, and Turkey. In most of these countries (except for France, Hungary, Romania, and Spain), the PEPP could serve as an alternative to household liquid assets. However, in Croatia, France and Italy, it was recognised as competing with existing domestic retirement and life insurance products, which may negatively impact its development. This is the first comprehensive study of the prospects of PEPP in a large group of countries. The results provide socially essential knowledge as they address the role of private savings in supplementing households’ future income from public pension schemes, considering the availability of a new product such as PEPP.